Relation of the eighth edition of the American Joint Committee on Cancer staging system with histological risk classification for primary eyelid basal cell carcinoma. Issue 3 (May 2021) - Savino, Gustavo; Volpe, Giulio; Grimaldi, Gabriela; Battendieri, Remo; Midena, Giulia; Lanni, Vittoria; Bernardo, Roberta; Iuliano, Adriana
Purpose: To investigate the relation between the eighth edition of the American Joint Committee on Cancer staging system and histological risk classification for primary eyelid basal cell carcinoma. Methods: Retrospective, observational case series of patients undergoing excisional biopsy for primary eyelid basal cell carcinoma in two tertiary centres between 2008 and 2018. Patients with <6 months of follow-up were excluded. Outcomes measured included histological subtype, American Joint Committee on Cancer 7 and 8 staging. Results: A total of 222 cases were included over a 10-year period, with a mean (range) follow-up of 25.74 (6–120) months and a median (range) age of 70 (28–93) years. According to American Joint Committee on Cancer 8, the most common T category was T1a (64%), followed by T1b (18%) and T2a (8%). Of the 222 specimens, 183 (82.43%), 17 (7.66%), 19 (8.56%) and 3 (1.35%) were staged as IA, IB, IIA and IIB, respectively. The most common histological subtype was nodular in IA category and infiltrative in categories IB and IIA. Histologically, low-risk basal cell carcinomas were related to lower American Joint Committee on Cancer staging (IA), whereas high-risk basal cell carcinomas were related to American Joint Committee on Cancer stages IB and IIA (p < 0.001). No significant relation was found between T categorisation and risk stratification when adopting American Joint Committee on Cancer 7. Conclusion: American Joint Committee on Cancer 8 staging system is strongly related to primary eyelid basal cell carcinoma histological risk classification.